Next-generation sequencing in thymic epithelial tumors uncovered novel genomic aberration sites and strong correlation between TMB and MSH6 single nucleotide variations. (28th April 2020) - Chen, Kai; Che, Jiaming; Zhang, Xianfei; Jin, Runsen; Xiang, Jie; Han, Dingpei; Sun, Yonghua; Gong, Ziying; Zhang, Daoyun; Li, Hecheng
Abstract: Thymic epithelial tumors (TET) including thymomas and thymic carcinomas are rare, but they are common primary tumors in the anterior mediastinum. The etiology and tumorigenesis of TET remain unclear. To better understand the novel aberrations of this rare tumor and provide more significant mutation sites for targeted therapy, we performed next-generation sequencing detection on 55 patients with TET. Our results showed that most genes in 12 core pathways harbored aberrations of indeterminate potential. In 4 genes ( ARID1A, KMT2C, TGFBR2 and MAP3K1), the indel frequency was above 90%. Dozens of genes, including TGFBR2, KMT2C, PRKDC, ATR, CHD2, SDHA, KDM5A, CHEK1, MSH6 and POLE, possessed frameshift indel with different frequencies in different hotspot sites, which could be the new targets of therapy for TET. For the first time, we revealed a strong correlation between the tumor mutational burden and single nucleotide variations, but not frameshift, on DNA mismatch repair gene MSH6 in TET. Highlights: Thymic epithelial tumors (TET) are rare; hence, identifying biomarkers is difficult. We performed next-generation sequencing (NGS) detection on 55 patients with TET. We found a diverse genomic mutation between TET subtypes and novel aberration sites. These aberration sites (frameshift indel) are for future therapy based on NGS.